ZAKAT INFAQ ALMS (ZIS) MOVEMENT MODEL AND GREEN ECONOMY: STUDY OF THE ROLE OF LAZISMU EAST JAVA - Kusuma, Kumara Adji; Lestari , Indah Dwi; Amelia, Ananda Mety; Wai, Khoong Tai (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to explore the role of Lazismu East Java in supporting the Green Economy through the management of zakat, infaq, and sedekah (ZIS) funds. Method: A qualitative approach is used to analyze the implementation of the ZIS movement model applied by Lazismu and its impact on sustainable development. Results: This study covers Lazismu programs, such as organic farming, waste management, renewable energy, and community economic empowerment. The results of the study indicate that Lazismu East Java has succeeded in integrating ZIS values with green economy principles, which have created positive impacts on both the environment and social welfare. However, this study also identified challenges, such as limited resources and community understanding of the Green Economy concept. Novelty: The ZIS movement model developed by Lazismu has great potential to be replicated by other zakat organizations, provided that there is increased capacity, cross-sector collaboration, and further education on the importance of sustainable development. These findings are expected to provide guidance for zakat institutions in playing a more significant role in supporting the Green Economy in Indonesia.